Semiotic Potret Perilaku Hedonisme Iklan ‘Sopir Keluarga Nissan Indonesia’: Analisis Semiotika Rolland Barthes - Agung Bungsu (KOMUNIDA : Media Komunikasi dan Dakwah, 2021)
Product marketing methods are increasingly diverse, for example automotive products. The intense competition from one automotive company to another makes the marketing field have to race with the ideas and ideas presented. The message that is constructed through advertising must be made as attractive as possible to steal the attention of the audience. An automotive product that tries to do marketing with a different idea is Nissan Indonesia. The ad is made by inserting a message of how warmth and happiness can be created in a family. This study aims to identify the signifier, signified and also the myths contained in Nissan Indonesia advertisements with the title "Sopir Keluarga" which tries to represent the life of today's hedonism. The research method used is semiotic analysis. The type of semiotics chosen is Rolland Barthes semiotics. The results of the study indicate that the overall myth found is hedonic behavior in the form of using branded goods. Then it was also found that excessive social media activity so as to form a lifestyle that allows a person to slip into arrogance and arrogance.